Integrated Single Stage Power Amplifier Based GaAs FET with Filter for Bluetooth Applications - Kahlan H. Hamid; Mohammed I. Dawod; Omar S. Abdulwahid (Tikrit Journal of Engineering Sciences)
This work presents the design, analysis, and simulation of a single-stage power amplifier integrated with a bandpass filter at 2.4 GHz. The embedded GaAs FET transistor, MGF2407A, in the Advanced Design System tool, is the heart of the amplifier circuit, operating in class AB mode at a drain-source voltage of 3.2 V and a gate-source voltage of -1.4 V. The source and load impedances have been extracted using the source and load-pull technique. Matching circuits were then designed and optimized at the input and output of the transistor. The simulated stability factor of the amplifier exceeded 3 in the frequency band from 2 to 3 GHz, with a maximum value of 4.27 at 2.4 GHz. The maximum simulated power gain and Power-Added Efficiency were 12.7 dB and 68.78%, respectively, at 2.4 GHz, with very low reflection coefficients at the input and output sides, with values below -23 dB. The amplifier was capable of delivering an output power of 5 dBm and 22 dBm at input power -10 dBm and 7 dBm, respectively, which meet the requirements of long-distance Bluetooth and long-term evolution applications. Simulation results also showed that the amplifier had a wide bandwidth of 100 MHz and an acceptable size area of 57 x 32 mm2. The amplifier circuit model reported here can be used to design and fabricate different amplifier circuits for a range of applications.